Catalyst for the production of butadiene from ethanol, process for its preparation and use

CN122875286APending Publication Date: 2026-10-09BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611366131.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了克服现有技术存在的乙醇制丁二烯催化剂在工业乙醇条件下易被水、有机酸等极性杂质毒化,导致Lewis酸活性位失活、乙醛缩合及MPV反应效率降低、乙烯及积碳等副反应增加的问题,提供一种乙醇制丁二烯用催化剂,该催化剂具有在工业乙醇中稳定性好、丁二烯选择性强、抗杂质毒化能力优异的特点

Benefits of technology

本发明通过在SiO2载体表面先构建碱性占位层,占据部分载体表面羟基位点,减少亲水性羟基的数量;再在剩余羟基位点引入过渡金属活性位点并与载体表面羟基形成锚定键合,确保活性组分的稳定负载;最后在催化剂最外表面接枝有机疏水层,显著降低催化剂表面的亲水性。通过碱性占位层、过渡金属活性位点与有机疏水层的协同作用,有效抑制了工业乙醇中水及极性杂质在催化剂界面的富集和竞争吸附,大幅提升了催化剂在工业乙醇条件下的抗杂质毒化能力和运行稳定性,同时保证了Lewis酸活性位点对乙醇制丁二烯串联反应的高效催化,具有优异的丁二烯选择性和较长的催化剂寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

This invention relates to the field of catalyst technology, and discloses a catalyst for the production of butadiene from ethanol, its preparation method, and its application. The catalyst comprises a SiO2 support, an alkaline occupant layer supported on the surface of the SiO2 support, transition metal active sites on the surface of the SiO2 support not covered by the alkaline occupant layer and anchored to hydroxyl groups on the support surface, and an organic hydrophobic layer grafted onto the outermost surface of the catalyst. The alkaline metal element in the alkaline occupant layer is selected from Mg and / or La, and the transition metal element in the transition metal active sites is selected from at least one of Ta, Nb, and Zr. The organic hydrophobic layer contains organosilane molecules. Through the synergistic effect of the alkaline occupant layer, the transition metal active sites, and the organic hydrophobic layer, this catalyst effectively inhibits the enrichment and competitive adsorption of water and polar impurities in industrial ethanol at the catalyst interface, exhibiting excellent resistance to impurity poisoning, butadiene selectivity, and operational stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to a catalyst for the production of butadiene from ethanol, its preparation method, and its application. Background Technology

[0002] Ethanol-to-butadiene (ETB) is an important non-petroleum route for synthesizing butadiene, which is of great significance for alleviating butadiene resource shortages and promoting the high-value utilization of biomass resources. Currently, ETB catalytic systems are mainly based on Lewis acid components such as Ta, Zr, and Nb, converting ethanol to butadiene through a series of reaction steps including catalytic ethanol dehydrogenation, acetaldehyde condensation, and MPV transfer hydrogenation.

[0003] Most existing ETB catalytic systems have been developed and evaluated based on analytical grade or anhydrous ethanol conditions, lacking research on their compatibility with real bio-based fermented ethanol. However, industrially widely used bio-based industrial ethanol typically contains polar impurities such as water (20%-40%), organic acids (e.g., acetic acid), aldehydes, and fusel oils. These polar impurities pose a serious threat to the stability of the catalyst.

[0004] Studies have shown that the Lewis acid catalytic sites such as Ta, Zr, and Nb in existing ETB catalysts are mostly coordinate-unsaturated structures, exhibiting high affinity for polar molecules. In industrial ethanol systems, polar impurities such as water and acetic acid readily compete with reactants (ethanol and acetaldehyde) for adsorption, occupying Lewis acid active sites and causing them to be covered, thereby reducing the catalytic efficiency of acetaldehyde condensation and the MPV reaction. Simultaneously, the deactivation of active sites exacerbates side reactions such as ethylene formation, by-polymerization, and coking, leading to decreased butadiene selectivity and shortened catalyst lifetime.

[0005] Furthermore, most existing catalysts are directly constructed on the surface of hydrophilic SiO2 supports. The SiO2 support surface contains a large number of continuously distributed silanol (Si-OH) sites. These continuous hydroxyl groups readily form hydrogen bond networks of water molecules through hydrogen bonding interactions, leading to the continuous enrichment of water and polar impurities at the catalytic interface, further exacerbating the coverage and deactivation of Lewis acid sites. The stability and selectivity of existing catalysts under industrial ethanol conditions are insufficient to meet practical application requirements. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems existing in the prior art where ethanol-to-butadiene catalysts are easily poisoned by polar impurities such as water and organic acids under industrial ethanol conditions, leading to deactivation of Lewis acid active sites, reduced efficiency of acetaldehyde condensation and MPV reaction, and increased side reactions such as ethylene and carbon deposition. The invention provides a catalyst for ethanol-to-butadiene production, which has the characteristics of good stability in industrial ethanol, strong butadiene selectivity, and excellent resistance to impurity poisoning.

[0007] To achieve the above objectives, the present invention provides a catalyst for the production of butadiene from ethanol, the catalyst comprising: SiO2 support; an alkaline occupant layer loaded on the surface of the SiO2 support for occupying some hydroxyl sites; and transition metal active sites loaded on the surface of the SiO2 support in areas not covered by the alkaline occupant layer and anchored to the hydroxyl groups on the support surface, wherein the transition metal active sites are formed by alkoxide precursors. And an organic hydrophobic layer grafted onto the outermost surface of the catalyst; The alkaline metal element in the alkaline occupant layer is selected from Mg and / or La; the transition metal element in the transition metal active site is selected from at least one of Ta, Nb and Zr; and the organic hydrophobic layer contains organosilane molecules.

[0008] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst for the production of butadiene from ethanol, comprising the following steps: (1) SiO2 support is impregnated with alkaline metal salt solution and subjected to a first heat treatment to form an alkaline occupancy layer on the surface of the SiO2 support to obtain precursor I; (2) The precursor I is impregnated with a transition metal precursor solution and subjected to a second heat treatment to form transition metal active sites on the surface of the precursor I, thereby obtaining precursor II; (3) The precursor II and organosilane are subjected to silanization and a third heat treatment in sequence to obtain the catalyst; the outermost surface of the catalyst is grafted with an organic hydrophobic layer; Wherein, the alkaline metal element in the alkaline metal salt is selected from Mg and / or La; the transition metal precursor is an alkoxide, wherein the transition metal element is selected from at least one of Ta, Nb and Zr.

[0009] A third aspect of the present invention provides a catalytic method for the production of butadiene from ethanol, comprising: Ethanol feedstock is introduced into a reactor and comes into contact with the catalyst described in the first aspect of the present invention. The reaction is carried out under the conditions of a reaction temperature of 275-380°C, a reaction pressure of 0.1-1.0 MPa, and a feed rate of 0.3-0.8 mL / h to produce butadiene.

[0010] Through the above technical solution, the present invention achieves the following beneficial effects: This invention first constructs an alkaline occupant layer on the surface of a SiO2 support, occupying some of the hydroxyl sites on the support surface and reducing the number of hydrophilic hydroxyl groups. Then, transition metal active sites are introduced into the remaining hydroxyl sites to form anchoring bonds with the hydroxyl groups on the support surface, ensuring stable loading of the active components. Finally, an organic hydrophobic layer is grafted onto the outermost surface of the catalyst, significantly reducing the hydrophilicity of the catalyst surface. Through the synergistic effect of the alkaline occupant layer, transition metal active sites, and organic hydrophobic layer, the enrichment and competitive adsorption of water and polar impurities in industrial ethanol at the catalyst interface are effectively suppressed, significantly improving the catalyst's resistance to impurity poisoning and operational stability under industrial ethanol conditions. Simultaneously, it ensures the efficient catalysis of the Lewis acid active sites for the tandem reaction of ethanol to butadiene, exhibiting excellent butadiene selectivity and a long catalyst lifetime. Detailed Implementation

[0011] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0012] In one aspect, this invention provides a catalyst for the production of butadiene from ethanol, the catalyst comprising: SiO2 support; an alkaline occupant layer loaded on the surface of the SiO2 support for occupying some hydroxyl sites; and transition metal active sites loaded on the surface of the SiO2 support in areas not covered by the alkaline occupant layer and anchored to the hydroxyl groups on the support surface, wherein the transition metal active sites are formed by alkoxide precursors. And an organic hydrophobic layer grafted onto the outermost surface of the catalyst; The alkaline metal element in the alkaline occupant layer is selected from Mg and / or La; the transition metal element in the transition metal active site is selected from at least one of Ta, Nb and Zr; and the organic hydrophobic layer contains organosilane molecules.

[0013] In this invention, the SiO2 support is preferably a spherical, strip-shaped, or irregularly shaped particle with a mesoporous structure, and its specific surface area is preferably 100-200 m². 2 / g, with a preferred pore volume of 0.75-2cm³. 3 / g, with an average pore size preferably of 5-30 nm. The support can be pretreated before use, for example, by calcining at 480-520℃ for 1-3 hours at a rate of 2-5℃ / min to remove physically adsorbed water, providing sufficient bonding sites for subsequent alkaline occupancy and anchoring of active components; the SiO2 support can be one or more of commercially available silica gel, mesoporous silica, or fumed silica.

[0014] In this invention, the alkaline occupant layer is loaded onto the surface of the SiO2 support, and its main function is to occupy some hydroxyl sites. This invention preferably selects Mg and / or La as the alkaline metal element because, during the heat treatment process, the alkaline metal element chemically bonds with the acidic isolated hydroxyl groups (-OH) on the SiO2 support surface, forming Mg-O-Si or La-O-Si bonded structures, thereby consuming a portion of the continuously distributed silanol groups. This effect effectively interrupts the path for water molecules to form a hydrogen bond network on the support surface, reducing the support surface's affinity for and enrichment of polar water molecules. Simultaneously, the presence of the alkaline occupant layer can regulate the acidity / alkalinity of the support surface, which is beneficial for inhibiting the formation of byproducts such as ethylene.

[0015] In some preferred embodiments, the mass percentage of the alkali metal element is 0.04-5%, preferably 1-1.5%, based on the mass of the SiO2 support.

[0016] In this invention, the transition metal active sites are loaded on the SiO2 support surface in the region not covered by the alkaline occupant layer, and form anchored bonds with the hydroxyl groups on the support surface. Preferably, the transition metal element in the transition metal active sites is selected from at least one of Ta, Nb and Zr.

[0017] According to the present invention, Ta, Nb, and Zr are highly efficient Lewis acid catalytic active components for the tandem reaction of ethanol to butadiene. These transition metal active sites are not simply deposited on the support surface, but rather achieve a highly stable dispersion by forming chemical anchoring bonds (such as MO-Si bonds, where M represents Ta, Nb, or Zr) with the remaining isolated hydroxyl groups on the support surface that are not occupied by the basic occupant layer. This anchoring structure endows the active sites with extremely high resistance to migration and aggregation. Therefore, preferably, based on the mass of the SiO2 support, the mass percentage content of the transition metal elements (Ta, Nb, and / or Zr) is 1-10%, preferably 7-8%.

[0018] In this invention, the organic hydrophobic layer is grafted onto the outermost surface of the catalyst, which may refer to the geometrical outer surface of the catalyst and the inner surface of the pores. Preferably, the organic hydrophobic layer contains organosilane molecules, preferably provided by silanes containing methyl groups, and more preferably methyltrimethoxysilane and / or phenyltrimethoxysilane.

[0019] According to the present invention, preferably, the surface hydroxyl density of the catalyst is ≤4.0 OH / nm. 2 The catalyst exhibits a water contact angle ≥ 84°. A lower surface hydroxyl density indicates fewer hydrophilic sites on the support surface, reducing the likelihood of polar impurity accumulation. A larger water contact angle indicates stronger hydrophobicity of the catalyst and a more pronounced repulsion effect on water molecules. Catalysts meeting these parameter ranges can effectively resist the poisoning effects of water and polar impurities in industrial ethanol, thus demonstrating excellent long-term operational stability. In this invention, for example, the surface hydroxyl density of the catalyst is 2-2.5 OH / nm. 2 Water contact angle ≥90°.

[0020] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst for the production of butadiene from ethanol, the method comprising the following steps: (1) SiO2 support is impregnated with alkaline metal salt solution and subjected to a first heat treatment to form an alkaline occupancy layer on the surface of the SiO2 support to obtain precursor I; (2) The precursor I is impregnated with a transition metal precursor solution and subjected to a second heat treatment to form transition metal active sites on the surface of the precursor I, thereby obtaining precursor II; (3) The precursor II and organosilane are subjected to silanization and third heat treatment in sequence to obtain the catalyst; the outermost surface of the catalyst is grafted with an organic hydrophobic layer.

[0021] Wherein, the alkaline metal element in the alkaline metal salt is selected from Mg and / or La; the transition metal precursor is an alkoxide, wherein the transition metal element is selected from at least one of Ta, Nb and Zr.

[0022] According to the present invention, in step (1), the alkaline metal salt in the alkaline metal salt solution is preferably selected from magnesium nitrate and / or lanthanum nitrate; preferably, the concentration of the alkaline metal salt solution is 0.02-0.1 mol / L, more preferably 0.04-0.08 mol / L.

[0023] The aforementioned nitrates readily decompose into their corresponding oxides during subsequent heat treatment, and the escape of nitrogen oxide gases generated during decomposition facilitates the formation of a porous structure, which is beneficial for the dispersion of the active components. The impregnation treatment can be performed using either an equal-volume impregnation method or an excess impregnation method, with an impregnation time of 0.5-6 hours at room temperature (25-35℃).

[0024] According to the present invention, in a preferred embodiment, step (1) includes: collecting the solid phase I after impregnation treatment, and performing a first drying treatment and a first heat treatment; The preferred drying conditions include a temperature of 70-90°C and a time of 10-15 hours. These conditions can effectively remove the solvent from the impregnation solution and prevent the solvent from evaporating rapidly during subsequent high-temperature calcination, which could lead to uneven distribution of the active components. The preferred conditions for the first heat treatment include: a temperature of 450-550°C and a time of 3-5 hours. This temperature range is sufficient to completely decompose the nitrate into oxides, while ensuring that the alkaline component and the carrier hydroxyl group undergo sufficient chemical interaction to form a stable alkaline occupancy layer; the heat treatment atmosphere is air or nitrogen.

[0025] According to the present invention, in step (2), the transition metal precursor in the transition metal precursor solution is preferably selected from at least one of tantalum ethoxide (Ta(OC2H5)5), niobium ethoxide (Nb(OC2H5)5), and zirconium ethoxide (Zr(OC2H5)4); preferably, the concentration of the transition metal precursor solution is 0.02-0.1 mol / L, more preferably 0.04-0.08 mol / L.

[0026] In some preferred embodiments, in step (2), the solid phase II after impregnation is collected and subjected to a second drying treatment and a second heat treatment; the conditions for the second drying preferably include a temperature of 70-90°C and a time of 10-15 h. The impregnation treatment can also be performed by an equal-volume impregnation method, in which the precursor I is impregnated in an organic solution of the transition metal precursor for 0.5-6 h at room temperature or under slight heating conditions.

[0027] In this invention, the conditions for the second heat treatment preferably include: a temperature of 450-550°C and a time of 3-5 hours. These drying and heat treatment conditions are similar to those in step (1), which can effectively decompose the precursor and stabilize the anchoring bond between the active site and the carrier; the heat treatment atmosphere is air, nitrogen, or an inert gas, preferably nitrogen or argon, to avoid excessive oxidation of the transition metal.

[0028] According to the present invention, in a preferred embodiment, in step (3), the silanization treatment involves contacting the precursor II with an organosilane; the organosilane molecules undergo a condensation reaction with the residual hydroxyl groups on the surface of the precursor II to form a hydrophobic graft layer. The silanization treatment is carried out at a temperature of 20-60°C for 1-8 hours. These mild reaction conditions help control the degree of silane molecule grafting and prevent excessive polymerization that could clog pores. The silanization treatment can be performed in an organic solvent (such as toluene, n-hexane, or anhydrous ethanol) or via gas-phase silanization. After the reaction is complete, the silanized product is obtained by filtration or centrifugation. More preferably, the silanization treatment is carried out at a temperature of 25-40°C for 3-5 hours.

[0029] According to the present invention, after the reaction is completed, the silanized product is obtained by filtration or centrifugation and washed 2-4 times with anhydrous ethanol to remove unreacted organosilanes and physically adsorbed organic matter; then, a drying treatment is performed, preferably at a temperature of 70-90°C for 10-15 hours, to fully remove the solvent remaining during the washing process; finally, a third heat treatment is performed at a temperature of 150-250°C for 1-3 hours to further stabilize the surface organosilicon structure, so that the silanization condensation reaction is completed, and at the same time, the physically adsorbed silane molecules are removed.

[0030] In some preferred embodiments, the mass ratio of precursor II to organosilane is preferably 1:0.2-0.6, and more preferably 1:0.4-0.5.

[0031] The third aspect of the present invention provides a catalytic method for producing butadiene from ethanol, the method comprising: introducing ethanol feedstock into a reactor, contacting it with the above-mentioned catalyst, and reacting it under the conditions of a reaction temperature of 275-380℃, a reaction pressure of 0.1-1.0MPa, and a feed rate of 0.3-0.8mL / h to generate butadiene; The ethanol feedstock can be, for example, industrial ethanol with an ethanol content of 60wt%-95wt%, or anhydrous ethanol. The reactor can be a fixed-bed reactor, a fluidized-bed reactor, or a slurry-bed reactor, preferably a fixed-bed reactor. Before the reaction, the catalyst can be activated at 300-500℃ for 1-3 hours under an inert atmosphere (such as nitrogen or argon). After condensation and separation, the butadiene can be purified by distillation or selective absorption.

[0032] The present invention will be described in detail below through embodiments.

[0033] The SiO2 carrier used was a commercially available product from McLean Industries, brand name S818464, with a specific surface area of ​​200 m². 2 / g; Magnesium nitrate, lanthanum nitrate, tantalum ethoxide, niobium ethoxide, and methyltrimethoxysilane are all commercially available analytical grade reagents.

[0034] Example 1 This embodiment illustrates the catalyst and its preparation method provided by the present invention, including: (1) The SiO2 support was placed in a muffle furnace and calcined at 500℃ for 2h at a rate of 2℃ / min in air atmosphere for pretreatment; 10g of the pretreated SiO2 support was placed in a 0.05 mol / L Mg(NO3)2·6H2O solution and impregnated at room temperature (25℃, the same below) for 2h using an equal volume impregnation method; after filtration, solid phase I was collected and dried at 80℃ for 12h, and then heat-treated at 500℃ for 4h to form an alkaline occupancy layer (MgO) on the surface of the SiO2 support. x ), thus obtaining precursor I; (2) Precursor I was placed in an ethanol solution of 0.05 mol / L tantalum ethoxide and impregnated at room temperature for 2 h; after filtration, solid phase II was collected and dried at 80 °C for 12 h, and then heat-treated at 500 °C for 4 h to form transition metal active sites (Ta) on the surface of precursor I, thus obtaining precursor II. (3) After mixing 0.2 mL of deionized water and 9.3 mL of anhydrous ethanol evenly, add 0.5 mL of methyltrimethoxysilane (MTMS) to prepare a 5% (v / v) MTMS modified solution. Then, add 1 g of precursor II at room temperature and perform silanization treatment at 25 °C for 4 h. After the reaction is completed, filter and collect the silanization product and wash it with anhydrous ethanol. Then, dry it at 80 °C for 12 h and heat-treat it at 200 °C in air for 2 h to obtain catalyst A1 with an organic hydrophobic layer grafted on the outermost surface.

[0035] Example 2 The catalyst was prepared according to the method of Example 1, except that the alkaline metal salt solution was adjusted to a 0.025 mol / L Mg(NO3)2·6H2O solution; the other conditions and steps were the same as in Example 1, and catalyst A2 was obtained.

[0036] Example 3 The catalyst was prepared according to the method of Example 1, except that the alkaline metal salt solution was adjusted to a 0.025 mol / L La(NO3)3·xH2O solution; the other conditions and steps were the same as in Example 1, and catalyst A3 was obtained.

[0037] Example 4 The catalyst was prepared according to the method of Example 1, except that the transition metal precursor solution was adjusted to be an ethanol solution of 0.025 mol / L tantalum ethoxide; the other conditions and steps were the same as in Example 1, and catalyst A4 was obtained.

[0038] Example 5 The catalyst was prepared according to the method of Example 1, except that the transition metal precursor solution was adjusted to be an ethanol solution of 0.025 mol / L niobium ethanol; the other conditions and steps were the same as in Example 1, and catalyst A5 was obtained.

[0039] Example 6 The catalyst was prepared according to the method of Example 1, except that in step (3), 0.25 mL of methyltrimethoxysilane MTMS was used instead of 0.5 mL of methyltrimethoxysilane MTMS; the remaining conditions and steps were the same as in Example 1, and catalyst A6 was obtained.

[0040] Example 7 The catalyst was prepared according to the method of Example 1, except that in step (3), the silanization treatment conditions included: a temperature of 60 °C and a time of 1 h; the other conditions and steps were the same as in Example 1, and catalyst A7 was obtained.

[0041] Comparative Example 1 The catalyst was prepared according to the method of Example 1, except that the transition metal precursor in step (2) was replaced with zirconium nitrate (Zr(NO3)4), that is, an inorganic salt was used instead of an alkoxide precursor. The other conditions were the same as in Example 1, and catalyst B1 was obtained.

[0042] Comparative Example 2 The catalyst was prepared according to the method of Example 1, except that the silanization treatment in step (3) was not performed, and the other conditions were the same as in Example 1, to obtain catalyst B2.

[0043] Comparative Example 3 The catalyst was prepared according to the method of Example 1, except that the construction of the alkaline occupant layer in step (1) was not performed (i.e., the SiO2 support surface was not loaded with alkaline metal elements). The other conditions and steps were the same as in Example 1, and catalyst B3 was obtained.

[0044] Test Example 1 The physical properties of the catalysts prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.

[0045] Test method: (1) The contents of alkali metal elements and transition metal elements were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES); (2) The number of hydroxyl groups on the catalyst surface was determined by thermogravimetric analysis (TGA), including: The sample was pretreated at 120 °C to remove physically adsorbed water from its surface; then, thermogravimetric analysis was performed at 800 °C under a nitrogen atmosphere at a heating rate of 10 °C / min.

[0046] During the high-temperature process, the hydroxyl groups on the sample surface undergo a dehydroxylation condensation reaction: 2Si-OH Si-O-Si + H2O; The number of hydroxyl groups on the sample surface is calculated based on the mass loss corresponding to the dehydroxylation stage.

[0047] The amount of water removed is calculated based on weight loss: nH2O = ; in, nH2O: The amount of water removed; Δm: Mass change during the dehydroxylation process; 18: Molar mass of water; Since 2 mol of surface hydroxyl groups are consumed for every 1 mol of water generated, the number of moles of surface hydroxyl groups is: nOH = 2 * nH2O; That is: nOH = 2* ; Further combining the specific surface area obtained from the BET test, the hydroxyl density per unit area was calculated: DOH = ; in, DOH: Surface hydroxyl density (OH / nm) 2 ); NA: Avogadro's constant (6.022 × 10²³ mol) -1 ); SBET: Sample specific surface area (m²) 2 / g); m: Mass of the test sample (g); 10*10^18: m 2 With nm 2 Conversion factors between them.

[0048] Table 1

[0049] Test Example 2 The catalysts prepared in the above examples and comparative examples were tested for catalytic performance. Their ethanol conversion rate and butadiene selectivity were evaluated under the conditions of industrial ethanol (ethanol content of 95 wt%) and anhydrous ethanol feedstock, respectively. The specific results are shown in Table 2.

[0050] Test method: In a fixed-bed reactor, anhydrous ethanol / industrial ethanol was used as raw material (feed rate 0.5 mL / h, nitrogen carrier gas flow rate 30 mL / min) and catalytic reaction was carried out at a reaction temperature of 380℃ and atmospheric pressure (0.1 MPa). The ethanol conversion rate and butadiene selectivity were measured in the initial stage of the reaction (2 h after the start of the reaction).

[0051] Table 2

[0052] The results from Tables 1 and 2 show that: As shown in Table 1, the surface hydroxyl density of the catalysts in each embodiment is ≤4.0 OH / nm. 2 The water contact angles of all samples were ≥84°, while the surface hydroxyl density of the comparative sample 2, which lacked a hydrophobic layer, was as high as 4.48 OH / nm. 2 The water contact angle of the first example is only 62.3°, while the comparative example 3, lacking an alkaline occupancy layer, has a water contact angle of 86.5° and a surface hydroxyl density of 2.63 OH / nm. 2 This indicates that both the organic hydrophobic layer and the alkaline occupant layer contribute to reducing surface hydrophilicity.

[0053] As shown in Table 2, Example 1, within the preferred range, achieved a conversion rate of 84.59% and a selectivity of 72.64% under industrial ethanol conditions, significantly superior to Comparative Example 2 without a grafted hydrophobic layer and Comparative Example 3 without a constructed alkaline site layer, proving that both are indispensable. Comparative Example 1 used zirconium nitrate instead of zirconium ethoxide, and its macroscopic properties (water contact angle 90.6°, surface hydroxyl density 2.45 OH / nm) were satisfactory. 2 Although similar to Example 4, the butadiene selectivity in industrial ethanol (57.39%) was much lower than that in Example 4 (69.71%), and the performance difference between anhydrous ethanol and industrial ethanol was even greater, indicating that the non-alkoxide precursor could not form a stable anchored bond structure and the active site was more easily deactivated in the aqueous system.

[0054] Furthermore, the performance differences between the various embodiments under industrial ethanol and anhydrous ethanol conditions are small, further demonstrating that the catalyst of the present invention has excellent tolerance to water and polar impurities in industrial ethanol.

[0055] In summary, this invention achieves significant technological progress through a three-layer synergistic structure consisting of an alkaline occupant layer, alkoxide-derived transition metal active sites, and an organic hydrophobic layer.

[0056] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A catalyst for the production of butadiene from ethanol, characterized in that, The catalyst includes: SiO2 support; An alkaline occupier layer loaded on the surface of the SiO2 support to occupy some of the hydroxyl sites; Transition metal active sites are loaded on the surface of the SiO2 support in regions not covered by the alkaline occupant layer and anchored to hydroxyl groups on the support surface. These transition metal active sites are formed by alkoxide precursors. And an organic hydrophobic layer grafted onto the outermost surface of the catalyst; The alkaline metal element in the alkaline occupant layer is selected from Mg and / or La; the transition metal element in the transition metal active site is selected from at least one of Ta, Nb and Zr; and the organic hydrophobic layer contains organosilane molecules.

2. The catalyst according to claim 1, wherein, Based on the mass of the SiO2 support, the mass percentage of the alkali metal element is 0.04-5%; And / or, based on the mass of the SiO2 support, the mass percentage of the transition metal element is 1-10%.

3. The catalyst according to claim 2, wherein, Based on the mass of the SiO2 support, the mass percentage of the alkali metal element is 1-1.5%; And / or, based on the mass of the SiO2 support, the mass percentage of the transition metal element is 7-8%.

4. The catalyst according to claim 1, wherein, The organosilane molecule is provided by a silane containing a methyl group.

5. The catalyst according to claim 4, wherein, The silane containing the methyl group is methyltrimethoxysilane and / or phenyltrimethoxysilane.

6. The catalyst according to claim 1, wherein, The surface hydroxyl density of the catalyst is ≤4.0 OH / nm 2 Water contact angle ≥84°.

7. The catalyst according to claim 6, wherein, The catalyst has a surface hydroxyl density of 2-2.5 OH / nm. 2 Water contact angle ≥90°.

8. A method for preparing a catalyst for the production of butadiene from ethanol according to any one of claims 1 to 7, wherein, Includes the following steps: (1) SiO2 support is impregnated with alkaline metal salt solution and subjected to a first heat treatment to form an alkaline occupancy layer on the surface of the SiO2 support to obtain precursor I; (2) The precursor I is impregnated with a transition metal precursor solution and subjected to a second heat treatment to form transition metal active sites on the surface of the precursor I, thereby obtaining precursor II; (3) The precursor II and organosilane are subjected to silanization and a third heat treatment in sequence to obtain the catalyst; the outermost surface of the catalyst is grafted with an organic hydrophobic layer; The alkaline metal element in the alkaline metal salt is selected from Mg and / or La; the transition metal precursor is an alkoxide, wherein the transition metal element is selected from at least one of Ta, Nb and Zr.

9. The method according to claim 8, wherein, The alkaline metal salt in the alkaline metal salt solution is selected from magnesium nitrate and / or lanthanum nitrate; the transition metal precursor in the transition metal precursor solution is selected from at least one of tantalum ethoxide, niobium ethoxide, and zirconium ethoxide.

10. The method according to claim 9, wherein, The concentration of the alkaline metal salt solution is 0.02-0.1 mol / L; And / or, the concentration of the transition metal precursor solution is 0.02-0.1 mol / L.

11. The method according to claim 10, wherein, The concentration of the alkaline metal salt solution is 0.04-0.08 mol / L; And / or, the concentration of the transition metal precursor solution is 0.04-0.08 mol / L.

12. The method according to claim 8, wherein, Step (1) includes: collecting the impregnated solid phase I, and performing a first drying treatment and a first heat treatment to obtain precursor I; The conditions for the first drying process include: a temperature of 70-90℃ and a time of 10-15 hours. The conditions for the first heat treatment include: a temperature of 450-550℃ and a time of 3-5 hours.

13. The method according to claim 8, wherein, Step (2) includes: collecting the impregnated solid phase II, and then performing a second drying treatment and a second heat treatment to obtain precursor II; The conditions for the second drying process include: a temperature of 70-90℃ and a time of 10-15 hours. The conditions for the second heat treatment include: a temperature of 450-550℃ and a time of 3-5 hours.

14. The method according to claim 8, wherein, In step (3), the temperature of the silanization treatment is 20-60℃ and the time is 1-8 h; the temperature of the third heat treatment is 150-250℃ and the treatment time is 1-3 h.

15. The method according to claim 14, wherein, The silanization treatment is performed at a temperature of 25-40 °C for 3-5 hours.

16. The method according to claim 15, wherein, The mass ratio of precursor II to organosilane is 1:0.2-0.

6.

17. The method according to claim 16, wherein, The mass ratio of precursor II to organosilane is 1:0.4-0.

5.

18. A catalytic method for the production of butadiene from ethanol, characterized in that, include: Ethanol feedstock is introduced into a reactor and contacted with the catalyst according to any one of claims 1 to 7. The reaction is carried out at a reaction temperature of 275-380℃, a reaction pressure of 0.1-1.0MPa, and a feed rate of 0.3-0.8mL / h to produce butadiene.